(untitled) (Fiep Bulletin - online, 2014)
This research aimed to investigate the contributions of Ballet in social and educational development of students in the class I ballet ballet Don Bosco in Campo Grande - M . The methodology used is of a qualitative, case study, with discursive analysis of the data obtained. Data were collected through semi-structured interviews, drawings and observations of lessons. We interviewed 10 students, female, eight years old, individually, after ballet class. Then, the students designed the ballet class, which served as a supplement during the analysis of the results obtained with the interview. Written texts dealing with the eight year old and their socializing agents. It also has as subject the classical ballet, its history in Brazil and the world, key positions and their contributions in the socialization of those who experience their practice. Still, history and a brief review of the Don Bosco Salesian College and Ballet Don Bosco. The data analysis was only possible after literature and literary study. The results confirmed that the ballet enabled social issues of students and their coexistence in society . Through the practice of ballet students increased their circle of friends and extended the knowledge from the exchange of experiences during lessons.